THE RELATIONSHIP BETWEEN SOCIAL ATTITUDE AND ETHICS OF ASSOCIATION WITH THE MORALS OF PHYSICS EDUCATION STUDENTS - Nuraeni, Nuraeni; Inthaud, Kullawat (EduFisika: Jurnal Pendidikan Fisika, 2024)
This study aims to describe how social attitudes, ethics of socializing, and noble morals, and whether there is a significant relationship between social attitudes and ethics of socializing with noble morals of physics education students. This study is a quantitative descriptive study. The sample of this study was 88 physics education students. The data analysis techniques used were descriptive statistics and inferential statistics for hypothesis testing. Based on the results of the study and descriptive analysis, the average score of social attitudes was 60.23 and the average score of social ethics was 65.26, each score was in the sufficient category, where seen from the most dominant assessment indicators, attitudes can be learned, and attitudes can change with an average value of 289.25, for social ethics, the most dominant assessment indicator was understanding and applying ethics with an average value of 297.75, and the average score of morals of physics education students was 65.67 which was also in the sufficient category, where seen from the most dominant assessment indicators, it was education with an average value of 317. The results of the inferential analysis showed that the Fcount value was 2624.45 while the Ftable at a significance level of 5% was 3.13. Thus, the Fcount value is much greater than the Ftable value, meaning that there is a significant relationship between social attitudes and social ethics with the morals of physics education students.